Food Price Volatility and Its Implications for Food Security and Policy - Kalkuhl, Matthias; von Braun, Joachim; Torero, Maximo; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2016)
This book provides fresh insights into concepts, methods and new research findings on the causes of excessive food price volatility. It also discusses the implications for food security and policy responses to mitigate excessive volatility. The approaches applied by the contributors range from on-the-ground surveys, to panel econometrics and innovative high-frequency time series analysis as well as computational economics methods. It offers policy analysts and decision-makers guidance on dealing with extreme volatility.
Foreword -- Introduction -- Part I: Food Price Volatility at International Food Commodity markets -- Part II: Commodity and Financial Market Linkages -- Part 3: National and Regional Response to Food Price volatility -- Part IV: the Micro-Economics of Price risk, volatility and Price shocks: Household, Firms and Communities.
Keywords: Agriculture$1 (BEconomic aspects.s; Agricultural Economics